Analysis of the Requirement for the Ships Using Methanol as Fuel - Michael Rachow; Steffen Loest; Agus Dwy Bramastha (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2018)
Methanol is a safe, cost-effective alternative marine fuel. It is one of promised solution for being shipping fuel because of it feedstock and produces less pollution than fossil fuel. Methanol is one of new fuel in the shipping industry; because of that there are lack of regulation for this fuel. IMO has not release regulation of using methanol as fuel but there is some draft is in process. The document that can be found to represent the draft of IMO IGF Code is report of Sub-Committee of Carriage Cargo and Containers (CCC) 3-3. Classification society that has the regulation for using methanol is LR and DNV GL. Comparing the three regulations and selecting the regulation that has high safety level is the best way to design the methanol-fueled ship. The result shows that there still some different opinion on the three regulations that regulate the methanol as ship fuel. Some regulation also doesn’t mention about the detail material that should be use in the system. Calculation method to selecting pipes thickness also different. To make it safe, the thick one should be used. Implementation the regulation on board ship resulting loses the payload of their cargo. The specific fuel consumption will be increased by factor 46% compared to fuel oil SFOC and the storage tank shall be protected by cofferdam that takes a lot of space. To safe ships space the service tank is recommended put in the main deck to prevent the use of protective cofferdam.